(untitled) (Journal of Naval Architecture and Marine Engineering, 2012)
Ship recycling in Bangladesh has been playing as a catalyst for the economy by supporting steel industry, shipbuilding industry and other industries and it has also been generating huge employments for the country. But, existing problems of this industry in terms of safety, health and environmental issues bring negative image for the country sometimes. This paper is aimed to identify the underlying problems of ship recycling industry and then analyze the nature of the problems to make it helpful overcoming the obstacles. A brief overview about strength, weakness, opportunity and threat of the industries in global perspective has been also discussed. DOI: http://dx.doi.org/10.3329/jname.v9i2.10515 Journal of Naval Architecture and Marine Engineering 9(2012) 91-102